Okomi, the new baby - Dorman, Helen; Dorman, Clive; Hutchings, Tony; Jane Goodall Institute (Nevada City, CA : Dawn Publications : In association with the Jane Goodall Institute, 2003)
Mama Du introduces her brand new baby, Okomi, to his father and the rest of the chimpanzee family group. Based on Jane Goodall's observations of chimpanzee behavior, with information about the endangered status of the animals.
3.2
K-3
Keywords: Chimpanzees -- Juvenile fiction; Chimpanzees -- Fiction; Animals -- Infancy -- Fiction; Chimpanzees -- Fiction; Animal babies -- Fiction